Efektifitas Pendidikan Kesehatan terhadap Sikap Hidup Bersih dan Sehat dalam Pencegahan Skabies di Pondok Pesantren Mukhtariyah Syafi'iyah 1 Beji Tuban - Titik Sumiatin; Binti Yunariyah (STIKes Patria Husada Blitar, 2017)
Scabies is known in Indonesia as skin diseases commonly known as a skin disease caused by infestation and sensitization to saccoptes scabiei. Scabies is also known as infectious disease worldwide with an estimated 300 million cases annually. This prevalence varies and fluctuates every time. The prevalence of scabies in Indonesia is around 6-27% of the general population. The purpose of this study was to determine changes in attitude about clean and health life of students after being given health education. The research design was Pre Experimental design. The population was all students in boarding school Mukhtariyah Shafi'ites 1 in Beji village, district. Jenu Kab. Tuban. The sample was 80 people determined by random sampling . The Data were collected using a questionnaire which is then analyzed by Spearman and Wilcoxon tests. The results showed attitude of boarding schoolstudents about clean and healthy life in preventing the scabies disease before being given health education and after being given health education has increased. The test results analysis using the Wilcoxon Sign Rank Test showed pretest and post-test yield value of p = 0.000 (<0.05), which means it's very significant. Health education was very effective in changing attitude of students, so it was advisable to further improve the implementation of health education at the boarding school in the district of Tuban.